CINTA AHLULBAIT DALAM KONTEKS KEBANGSAAN - Setiawan, Iwan (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
This research aimed to reveal the urgency of love for the  family of Prophet saw. (ahlulbait) within national context. The method used was literature study. This study found that love for ahlulbait were the main foundation of faith (especially among ahlussunnah wal-jamā'ah) and hatred of them must be avoided. In addition, national unity is the most important element that must be maintained by each party amidst the diversity of schools of thought, religion, belief, and existing ideas